Pengaruh Disiplin dan Stres Kerja terhadap Kinerja Karyawan Pada PT Tunas Ridean Tbk Cabang Ciputat Tangerang Selatan - Eti Ariyanti; Endang Susilo Wardani; Laila Irawati (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
Employee performance is one of the key factors that determine the success of an organization. In a competitive business environment, companies need employees who are disciplined, productive, and able to manage work pressure effectively. However, many organizations still face challenges related to low employee performance caused by a lack of work discipline and increasing levels of work stress. This research aims to determine the influence of discipline and work stress on employee performance at PT Tunas Ridean Tbk Ciputat Branch, both partially and simultaneously. This study uses a quantitative approach with a survey method. The population in this research consists of eighty-five employees who were all used as respondents through a census technique. Data were collected using a closed-ended Likert scale questionnaire distributed via WhatsApp groups and processed using SPSS version 27. The analysis included descriptive statistics, validity and reliability testing, classical assumption testing, and multiple linear regression analysis. The results show that discipline and work stress significantly affect employee performance both partially and simultaneously. High discipline encourages employees to be more responsible and productive, while excessive work stress tends to decrease performance. The study implies that companies should strengthen work discipline consistently while managing employee stress through supportive leadership and a healthy work environment.